INNOVATIVE TEXTILE RECYCLING TECHNOLOGIES AND THEIR IMPACT ON TRADE - YEVTUSHENKO, Valentyna; RASTORHUIEVA, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The modern textile industry is one of the largest consumers of natural resources and, at the same time, a significant source of industrial waste. Every year, a vast amount of textile products is disposed of, creating serious environmental burdens and economic losses. In response to these challenges, the global industry is transitioning to sustainable production and the active use of recycling technologies. The main solutions in this field include chemical and mechanical recycling, biotechnology, and circular fashion, which contribute to reducing the use of primary raw materials, lowering CO₂ emissions, and implementing the concept of a circular economy. Innovative textile recycling technologies reduce waste and create environmentally friendly materials for new production. Chemical recycling breaks textiles down into their primary components, mechanical recycling enables the reuse of raw materials, and biotechnology facilitates the creation of biodegradable materials. Circular fashion promotes the reuse of clothing, reducing demand for new products and supporting sustainable consumption. This article analyzes modern textile recycling approaches and their impact on international trade. The advantages of each technology are considered, including the ability to produce eco-friendly materials, improve secondary raw material quality, and increase demand for recycled products. Research findings indicate that actively implementing innovative textile recycling technologies fosters the growth of the eco-product market, reduces production costs, and opens new opportunities in trade. Investing in scientific research, creating economic incentives for companies, and raising consumer awareness of the benefits of recycled products will significantly accelerate the transition to a circular economy in the textile industry.